Architecture - Augmented reality techniques and use cases in architecture and urban planning. - Broschart, Daniel; Zeile, Peter (My University, 2014)
The current topics "Smart City" and "Smart Planning" do not just have to be about big solutions to make cities more efficient. There are also small solutions which can help planners and architects in their daily communication work, opening planning processes for more of the city's citizens and make the processes themselves smarter. The man-made environment affects every human who lives within it. Especially when changes are made within this environment, every citizen has to be able to form an opinion towards these changes. Not every person affected has a planning or architectural background though, so one has to expect that the spatial perception of each person is to be valued in a different way. Based on these various requirements the ways of internal and outside communication have to be adaptable, and offer an understandable transfer of relevant contents. The available tools are under constant development, resulting in new applications for communicating within the planning process. The focus concerning the communication techniques is on interactive tools. This paper gives a general overview of common augmented reality (AR)- techniques and their specific characteristics and tries to show possible use cases in the fields of architecture and urban planning. Besides the view on the technical development and the resulting use cases, the consequences and effects of the expansion of the repertoire of methods for planners and architects shall be discussed. The social significance and the resulting changes for urban planning as a whole are also relevant.
Keywords: Stadtplanung; Planungsprozess; Partizipation; Informationstechnologie; Kommunikationstechnologie; Planungsinstrument; Technikstand; Smart City; Visualisierung; Augmented reality; Smartphone